Integrative CUT&Tag-RNA-Seq analysis of histone variant macroH2A1-dependent orchestration of human induced pluripotent stem cell reprogramming - Liorni, Niccolò; Napoli, Alessandro; Castellana, Stefano; Giallongo, Sebastiano; Řeháková, Daniela; Re, Oriana Lo; Koutná, Irena; Mazza, Tommaso; Vinciguerra, Manlio (Epigenomics, 2023)
Aim: Human induced pluripotent stem cells (iPSCs) are inefficiently derived from somatic cells by overexpression of defined transcription factors. Overexpression of H2A histone variant macroH2A1.1, but not macroH2A1.2, leads to increased iPSC reprogramming by unclear mechanisms. Materials & methods: Cleavage under targets and tagmentation (CUT&Tag) allows robust epigenomic profiling of a low cell number. We performed an integrative CUT&Tag-RNA-Seq analysis of macroH2A1-dependent orchestration of iPSCs reprogramming using human endothelial cells. Results: We demonstrate wider genome occupancy, predicted transcription factors binding, and gene expression regulated by macroH2A1.1 during reprogramming, compared to macroH2A1.2. MacroH2A1.1, previously associated with neurodegenerative pathologies, specifically activated ectoderm/neural processes. Conclusion: CUT&Tag and RNA-Seq data integration is a powerful tool to investigate the epigenetic mechanisms occurring during cell reprogramming.
Keywords: sekvenování transkriptomu; Cellular Reprogramming; histony; přeprogramování buněk; lidé; Histones; indukované pluripotentní kmenové buňky; RNA-Seq; Induced Pluripotent Stem Cells; Transcription Factors; transkripční faktory; Endothelial Cells; endoteliální buňky; Humans